Pertimbangan Hakim Dalam Menjatuhkan Sanksi Pidana Terhadap Pelaku Kekerasan Seksual Yang Berusia Lanjut - Muh. Rivando Orfan; Wahyu Tris Haryadi, S.H., M.H. (Fakultas Hukum Universitas Bhayangkara Surabaya, 2024)
The phenomenon of sexual violence continues to show a significant upward trend, occurring in educational settings, within families, and across society at large. Such acts not only inflict physical and psychological trauma on the victims but also have the potential to hinder their development and contribution as the nation's future generation. One particular issue that has garnered public attention in this context is the involvement of elderly individuals as perpetrators of sexual violence. The advanced age of these offenders often presents distinct challenges for law enforcement officials in the process of upholding justice in Indonesia. This research constitutes an empirical study aimed at examining the judicial considerations employed by judges when imposing criminal sanctions on elderly perpetrators of sexual violence. The main objective of this study is to analyze the law enforcement process and identify the factors that form the basis of legal consideration towards elderly offenders in such criminal acts. The findings of this research indicate that judges' considerations in sentencing elderly perpetrators are influenced by multiple factors, including the physical and psychological condition of the offender, the severity of the crime, the impact on the victim, as well as the fundamental principles and objectives of criminal punishment. Nevertheless, the enforcement of legal measures against sexual violence involving elderly offenders remains a priority to ensure justice for the victims and to create a deterrent effect for the perpetrators, while also taking into account the specific conditions associated with advanced age within the criminal justice framework.